Affective responses across psychiatric disorders—A dimensional approach. (3rd June 2016) - Hägele, Claudia; Friedel, Eva; Schlagenhauf, Florian; Sterzer, Philipp; Beck, Anne; Bermpohl, Felix; Stoy, Meline; Held-Poschardt, Dada; Wittmann, André; Ströhle, Andreas; Heinz, Andreas
Highlights: We assessed emotion processing across nosological boundaries mental disorders. Pleasant stimuli activated the ventromedial prefrontal cortex across all subjects. Aversive stimuli activated the left amygdala across all subjects. We did not find significant group differences or a clear dimensional correlate. Abstract: Studying psychiatric disorders across nosological boundaries aims at a better understanding of mental disorders by identifying comprehensive signatures of core symptoms. Here, we studied neurobiological correlates of emotion processing in several major psychiatric disorders. We assessed differences between diagnostic groups, and investigated whether there is a psychopathological correlate of emotion processing that transcends disorder categories. 135 patient with psychiatric disorders (alcohol dependence, n = 29; schizophrenia, n = 37; major depressive disorder (MDD), n = 25; acute manic episode of bipolar disorder, n = 12; panic disorder, n = 12, attention deficit/hyperactivity disorder (ADHD), n = 20) and healthy controls (n = 40) underwent an functional magnetic resonance imaging (fMRI) experiment with affectively positive, aversive and neutral pictures from the International Affective Picture System (IAPS). Between-group differences were assessed with full-factorial ANOVAs, with age, gender and smoking habits as covariates. Self-ratings of depressed mood and anxiety were correlated with activation clusters showing significant stimulus-evoked fMRI activation. Furthermore, we examined functional connectivity with the amygdala as seed region during the processing of aversive pictures. During the presentation of pleasant stimuli, we observed across all subjects significant activation of the ventromedial prefrontal cortex (vmPFC), bilateral middle temporal gyrus and right precuneus, while a significant activation of the left amygdala and the bilateral middle temporal gyrus was found during the presentation of aversive stimuli. We did neither find any significant interaction with diagnostic group, nor any correlation with depression and anxiety scores at the activated clusters or with amygdala connectivity. Positive and aversive IAPS-stimuli were consistently processed in limbic and prefrontal brain areas, irrespective of diagnostic category. A dimensional correlate of these neural activation patterns was not found.